An Approximate Message Passing Algorithm for Channel and Impulsive Noise Estimation in Underwater Acoustic OFDM Systems - Wu, Shuyi; Wang, Shuche; He, Zhiqiang; Niu, Kai; Rong, Yue (OCEANS 2019 - Marseille, 2019)
An accurate and efficient channel and impulsive noise estimation is an important step in underwater acoustic (UA) orthogonal frequency-division multiplexing systems. We propose an approximate message passing (AMP) algorithm for channel and impulsive noise estimation. In particular, we model the distribution of the channel impulse response and impulsive noise as a Gaussian mixture, which is the prior information for the AMP algorithm. The proposed algorithm is evaluated through numerical simulations and real data collected during a UA communication experiment conducted in December 2015 in the estuary of the Swan River, Western Australia. The simulation and experimental results show that compared with existing approaches, the proposed algorithm has a better performance.